The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1128/iai.15.1.221-229.1977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low- and High-Passage Influenza Virus Infection in Normal and Nude Mice

Abstract: A human isolate of type A Hong Kong influenza virus (H3N2) was adapted to mice by serial passage. Lung homogenates from mice who received low passage levels contained about the same quantity of virus (10 6.2−6.95 50% tissue culture infective doses/ml) as those from mice who received high passage levels (10 5.95−6.45 50% tissue culture infective doses/ml); however, death occurred only in animals given high-passage virus. Passage 3 (P3) and passage 9 (P9) viruses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…The viral titers in the lungs and the hemagglutinin antibody titers did not differ in the two groups [14]. Wyde et al observed that athymic nude (T cell deficient) mice exhibited increased survival times and had less cell infiltration with no destruction of the lungs, compared with immune-competent control mice which suffered severe lung destruction [15]. The thymuses of the control mice were markedly reduced in size at the time of death, suggesting the depletion of cortical lymphocytes [10,15].…”
Section: Pathologic Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The viral titers in the lungs and the hemagglutinin antibody titers did not differ in the two groups [14]. Wyde et al observed that athymic nude (T cell deficient) mice exhibited increased survival times and had less cell infiltration with no destruction of the lungs, compared with immune-competent control mice which suffered severe lung destruction [15]. The thymuses of the control mice were markedly reduced in size at the time of death, suggesting the depletion of cortical lymphocytes [10,15].…”
Section: Pathologic Studiesmentioning
confidence: 99%
“…However, it is likely that the innate immune response plays a crucial role in influenza virus elimination from the host [5,17]. It has been reported that nude mice which have no T cells [15,25] and 'Rag2' knockout mice which lack an acquired immune system [26] showed a similar clinical course compared to wild type animals when infected with influenza viruses. In cotton rat models, virus specific T cells and antibodies appear after virus clearance in the airways and lung inflammatory response peaks after virus is cleared [5,27].…”
Section: Host Response To Viral Insultsmentioning
confidence: 99%
See 3 more Smart Citations